Systematically comparing methods used to study flow in sport: A longitudinal multiple-case study - Jackman, P. C.; Crust, L.; Swann, C. (Psychology of Sport and Exercise, 2017)
Objectives: The study aimed to evaluate the effectiveness of existing methods employed to collect experience-near data on flow in sport to develop a more robust approach to investigate the phenomenon in this context. Design: Longitudinal mixed method multiple-case study. Method: Ten Irish athletes (M age=25.12 years, SD±3.83) completed the Flow Questionnaire (FQ; Csikszentmihalyi & Larson, 1984) and the Flow State Scale-2 (FSS-2; Jackson & Eklund, 2004) following the completion of five competitive performances. Questionnaire responses were used to identify the occurrence of flow and sample individuals for event-focused interviews (total=22), which were conducted as soon as possible after performances (M=4.05 days). Data from the quantitative and qualitative phases were analysed independently prior to integrated dataset analysis using within-case and then cross-case analysis. Results: Flow and clutch states were described by participants during event-focused interviews. Conducting multiple event-focused interviews provided novel insights into similarities and differences in participant experiences across numerous performance contexts. Integration of the questionnaire and interview data revealed issues with the discriminant validity of the FQ and the FSS-2, as the questionnaire contents represented the subjective experience reported by participants during flow and clutch states. Conclusion: Findings highlight issues with the use of the FQ and FSS-2 to assess the flow experience and reinforce the importance of collecting qualitative data soon after performances until more valid quantitative measures are developed. The methodological issues that emerged are discussed in relation to the existing literature, and potential implications and recommendations for future research are outlined.